Teachers’ adaptation to the implementation of the Merdeka curriculum: A case study - Anisa, Ramelia Dwi; Fatmariza, Fatmariza (Indonesian Research Journal in Education |IRJE|, 2026)
The implementation of the Merdeka Curriculum represents a major reform in Indonesia’s education system, emphasizing flexible learning and student-centered instruction. This study aims to examine teachers’ adaptation to the implementation of the Merdeka Curriculum at SD Negeri 8 Lubuklinggau. A qualitative descriptive case study design was employed. Data were collected through semi-structured interviews with ten teachers teaching in Grades 1, 2, 4, and 5, as well as documentation analysis of teaching modules and learning materials. The data were analyzed using the interactive model of qualitative analysis, which comprises data reduction, data display, and conclusion drawing. The findings show that teachers have begun adapting by developing teaching modules, utilizing the Merdeka Mengajar Platform, and implementing more student-centered learning strategies. However, challenges remain, including limited instructional media, diverse student learning abilities, and the need for continuous professional development to support effective curriculum implementation, which can hinder the Merdeka Curriculum's overall success in enhancing student engagement and learning outcomes.